Coaches’ leadership behavior, motivational atmosphere and athletes’ motivational internalization: the perspective of self-determination theory - Haizhen Huang; Qian Zhang; Maozhu Jin (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Objective: The objective of this study is to examine the leadership behaviour of coaches and the relationship between the mastery motivational atmosphere and the respective sub-dimensions of basic psychological needs. This is done with a view to better solve the path selection and optimization problem noted in coaches' leadership behaviour’s effectiveness based on the self-determination theory. Methods: This research focuses on volleyball players and uses the maximum likelihood method to estimate the hypothetical model by ccarrying out the path coefficient significance test. Results: In the incentive atmosphere of cooperative learning, athletes will continue to find problems, correct mistakes, and improve their understanding of training and competition. Therefore, it is reasonable to assume that the training-related guidance of coaches plays a key role in the construction of an incentive atmosphere of cooperative learning. Conclusion: The coaches’ positive behaviours, tolerance of failure, and encouragement of attempts can help build a task-oriented motivational atmosphere, and through the transfer of athletes to realize the internalization of external incentives, athletes show a positive behaviour orientation.